The efficacy of a trivalent inactivated salmonella vaccine combined with the live s. gallinarum 9R vaccine in young layers after experimental infections with s. enteritidis, s. typhimurium, and s. infantis - Huberman, Yosef Daniel (2022)
Worldwide, poultry infections by Salmonella are the cause of significant economic losses, not only due to reduced production (due to fowl typhoid disease), but also considering the efforts and control measures that must be constantly applied, especially due to zoonotic serovars. Poultry is a common reservoir of Salmonella and its transmission into the food chain is a risk for humans. The vaccination of layers plays an important role in the overall efforts to prevent Salmonella infections. An inactivated trivalent vaccine was prepared with S. Enteritidis, S. Typhimurium, and S. Infantis strains. Infection trials were performed to evaluate the efficacy of three vaccination schedules using inactivated and live S. Gallinarum 9R vaccines. For this purpose, at week 5 of life, one subcutaneous dose of live S. Gallinarum 9R vaccine (1–5 × 107 CFU) was given to Groups 1 and 2. At weeks 8 and 11 of life, chickens were also vaccinated with one (Group 1) or two (Groups 2 and 3) intramuscular doses of the inactivated oil-adjuvant trivalent vaccine (1 × 108 CFU/dose of each antigen). Group 4 consisted of chickens that remained unvaccinated (control). At week 14 of life, the efficacy of the vaccination plans was evaluated in three separate inoculation trials with S. Enteritidis, S. Typhimurium, or S. Infantis. After vaccination with the inactivated vaccine, homologous antibody production was observed, and after challenge, a significant reduction in the faecal shedding, invasion, and colonization of S. Typhimurium and S. Infantis was achieved by all vaccination schedules, while the vaccination with at least one dose of the live S. Gallinarum 9R vaccine was necessary to obtain such a significant protection against S. Enteritidis infection.